A Case Study of Using Common and Proper Noun for Civil Engineering Students in University of Asahan - Harry Sambayu; Derliana Hasibuan; Lisa Fitri Meidipa (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study examines the competence of second-semester students at Asahan University in distinguishing and using common nouns and proper nouns effectively. Utilizing a qualitative research approach, interviews were conducted with 20 students from the Civil Engineering Department to assess their grammatical understanding. The findings indicate that 10 students demonstrated moderate proficiency, achieving an average score of 75, while the remaining students encountered difficulties in capitalization rules and contextual application. These results highlight the need for enhanced instructional strategies that integrate practical exercises and real-world applications to improve students' mastery of noun usage. This research contributes to broader discussions on English grammar education and its role in strengthening language proficiency among learners